Human factor in mental health and healing - Khan, Umeed Ali; Ismail, Haji M.; Musa, Ramli; Abdullah, Kartini; Ali, Syed Masroor; Helal Uddin, A.B.M. (2010)
The medical discipline is considered to possess two components. Its first component is scientific in nature and the other is artistic. The latter pertains to the relationship between the doctor and patient. The importance of doctor-patient relationship is illustrated by the phrase that ‘the treatment of a patient begins from the very first moments of the meeting with the doctor’. And also, more than half of the patients of those doctors who are confident of being most caring towards their patients, remain unsatisfied with the received care from such doctor’s. This article describes the author’s most rewarding experience with two of his psychotic patients with whom he attempted to optimize his relationship in the opening phase of his first interview with them. The emotionally touching appreciation expressed by these two patients was academically least expected and hence subsequently impacted the author’s approach to such patients in a remarkably significant way. A brief literature review is presented on the topic of the importance of human relationship in both mental health and healing.